Estimación de la huella hídrica, para la Secretaría del Agua Planta Central Quito - Guamán Eras, Juan Pablo (2018)
In Ecuador, the Secretariar of Water is the governing body of water resources, it is therefore essential to develop indicators for sustainable use of water, including the Water Footprint (HH) next to this institution, this indicator examines, describes and quantifies the direct and indirect use of consumption of water resources within the institution, either by activities, supplies or services required by the officials. The investigative project aimed to calculate the institutional HH for the year 2017 for Secretariat of Water, applied the methodology developed by Hoekstra, 2011 on the Water Foot Print Network (WFN), in four phases of study: establishment of objetives, accounting of water footprint sustainability assessment and formulation of response. With the aim of reducing the water footprint of the institution, in the final phase of the project raised and implemented strategies that guarantee the reduction of the use and consumption of the resource water. The study identified that the largest HH is concentrated in electricity consumption, adding a high consumption of coffee, tea and water bottle and a little awareness of the optimization of bond paper. The study shows that in our country the institutions that should promote the efficient use of water resources do not apply practices efficient to allow reducing the consumption of resources, and thus ensure the permanence of natural resources to future generations.